2016
DOI: 10.1097/wnp.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Multimodality Intraoperative Neurophysiological Monitoring Changes Between Spinal Intramedullary Ependymoma and Hemangioblastoma

Abstract: In our study, the incidence of transient changes in MEPs was higher in hemangioblastoma than in ependymoma. Our data suggest that it may be necessary to consider tumor features and the type of surgical technique used, particularly when interpreting intraoperative neurophysiologic monitoring profiles of intramedullary spinal cord tumors such as ependymomas and hemangioblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
(36 reference statements)
2
5
0
Order By: Relevance
“…The present results partially correlate with those of former publications. [36][37][38][39][40][41][42][43] Although sensitivity and NPV were on a comparable level as our results in most studies, specificity and PPV differed widely. Some studies reported a specificity or PPV > 90%; ours differed markedly.…”
Section: Discussion Predictive Value Of Ionm During Resection Of Isctsupporting
confidence: 59%
“…The present results partially correlate with those of former publications. [36][37][38][39][40][41][42][43] Although sensitivity and NPV were on a comparable level as our results in most studies, specificity and PPV differed widely. Some studies reported a specificity or PPV > 90%; ours differed markedly.…”
Section: Discussion Predictive Value Of Ionm During Resection Of Isctsupporting
confidence: 59%
“…For postoperative neurologic deterioration, the alert criteria for intraoperative MEP changes vary from 50% to 75% in amplitude reduction [ 4 ]. Some studies included amplitude criterion in addition to the latency criterion for SEP monitoring [ 4 19 20 ]. The specific alarm criteria in our spine hospital are a more than 50% reduction in MEP amplitude, and a more than 10% of N20 or P37 latency prolongation for SEPs.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study compared certain pathologic types of spinal cord tumors to identify which type easily affects the IONM alarm criteria [ 4 ]. Considering the signal pathways of MEPs and SEPs, the vulnerability to the tracts would differ by anatomical and pathologic types.…”
Section: Introductionmentioning
confidence: 99%
“…During resection of intramedullary, subdural and epidural tumors, MEP monitoring has become a true surgical technology ( 40 ). Recording and interpretation of MEPs is straightforward and fast.…”
Section: Discussionmentioning
confidence: 99%
“…Recording and interpretation of MEPs is straightforward and fast. During tumor separation procedures and during tumor resections, spinal cord and nerve roots may be damaged by vascular compromise, compression, traction or electric coagulation hemostasis ( 40 ). For detection of such potentially reversible damage, the function of the motor pathways must be assessed continuously with MEP monitoring.…”
Section: Discussionmentioning
confidence: 99%